Alarm Calling and Kinship - Stephan, Claudia; Zuberbühler, Klaus (Encyclopedia of Evolutionary Psychological Science, 2021)
Alarm calling is a widespread phenomenon in the animal kingdom, usually produced by individuals during predation attempts, a context with large fitness consequences, suggesting that the behavior has been under strong selection pressure. But there is something paradoxical about animal alarm calls. Why should an individual, faced with a potentially lethal predator, behave in conspicuous ways to warn others, rather than trying to escape or hide from the danger? This seemingly altruistic behavior has posed a major challenge for evolutionary theory and become the topic of countless studies. Two major research themes have been addressed with studies on animal alarm calls: the cognitive processes involved in call production and perception and the evolutionary forces that have shaped the behavior. The following sections...<br
Keywords: Alert call; Altruistic behavior; Kin selection; Warning call